Immersive videos of natural and urban environments can enhance awe and psychological well-being - Barth, Lisa L.; Mostajeran, Fariba; Steinicke, Frank; Riecke, Bernhard E.; Kühn, Simone (Frontiers in Virtual Reality, 2025)
Experiencing the emotion of awe has been associated with improvements in psychological wellbeing. This emotion can be systematically elicited in laboratory settings and immersive virtual reality (VR) has been shown effective for this purpose. In this work, we exposed 36 healthy participants to three immersive videos from natural and urban scenes (i.e., mountain, forest with waterfall, and city), and a 3D model of a neutral room as a baseline condition. These environments were compared in terms of self-reported levels of awe and clinically relevant aspects of psychological wellbeing, such as state depression and anxiety. In addition, we took the level of prior experience of the participants with VR into account and investigated whether the psychological effects hold for both novice and experienced VR users. The results suggest that exposure to all three immersive videos elevated the level of awe, reduced current states of depression, and increased positive affect compared to the baseline. We also discovered that, while the urban environment elicited the same amount of awe as both natural environments, only exposure to natural environments decreased current states of anxiety and negative affect. Finally, although experienced VR users had partly lower overall scores, prior experience did not reduce the relative benefits of exposure to immersive videos, as both experienced and novice users showed similar improvements compared to their respective baselines. Our findings can help guide future research and therapeutic applications that use immersive videos to harness the psychological benefits of experiencing awe.